El autocuidado y apoyo social de mujeres de un proyecto de seguimiento mamográfico en Porto Alegre/Brasil - Schneider Hermel, Júlia; Bones Rocha, Katia; Calderón Uribe, Magaly; Pizzinato, Adolfo (Psicooncología, 2016)
Objective: Identify preventive self-care practices and analyze the configurations of the network support for women with and without breast cancer registered in a mammography-monitoring project from Porto Alegre/Brazil.Method: a mixed sequential delimitation was performed, which expanded the results of the quantitative step (cross and correlation section) in a qualitative step (narrative interviews). 37 women diagnosed with breast cancer (group 1) and 72 without this diagnosis (group 2 – monitoring) participated. The following instruments were used: Assessment Questionnaire Self-care Ability (ASA-A) and Assessment Questionnaire Perceived Social Support and Community. There were performed descriptive analysis and comparison of means (t test and ANOVA) between the two groups. To deepen the understanding of the data, we selected four women with breast cancer with extreme levels on the scale of Social Support to participate in the biographical narrative interviews.Results: the analysis indicate that women who had breast cancer have better self-care practices than the women from the monitoring project (t = 1.791, P = 0.027). As for the analysis of social support, there were no statistically significant differences between the two groups. All participants have an average level of perceived social and community support. It was highlighted by the qualitative data that it was after the diagnosis of breast cancer that women lived self-care aspects they had not previously experienced.Conclusions: the self-care was significantly bigger in the group of women with breast cancer, where the cancer diagnosis was a trigger to increase self-care.
Keywords: Self-care; social support; breast cancer.